Airplane stability and control : - Abzug, Malcolm J. (Cambridge University Press, 2002)
The authors, widely known for their contributions to airplane design and development, have captured both the technological progress and the excitement of this important facet of aviation. This updated edition includes new developments in propulsion-controlled aircraft, fly-by-wire technology, redundancy management, applications, and safety. It is profusely illustrated with photographs and figures, and includes brief biographies of noted stability and control figures along with a core bibliography.